Removal of sunscreen compounds from swimming pool water using self-organized TiO2 nanotubular array electrodes - Esbenshade, Jennifer Lynne; Cardoso, Juliano Carvalho [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V. Sa, 2010)
An alternative method to remove sunscreen compounds 4-methylbenzylidene camphor (4-MBC), 3-benzophenone (BENZO) and 4-aminobenzoic acid (PABA) from swimming pool water is proposed based on photoeletrocatalytic oxidation using self-organized TiO2 nanotubular array electrodes irradiated by UV light. The best condition for the mineralization of these compounds was found to be 0.1 mol L-1 Na2SO4 at pH 9 with +1.5 V potential applied to the electrode. This leads to 100% removal of the 4-MBC, BENZO and PABA compounds in tap water, monitored by spectrophotometric and HPLC measurements and a maximum of 98.7%, 90.8% and 88.4% TOC reduction after a 3-h period of treatment. The method was successfully applied to sunscreen degradation in swimming pool water, reaching 100% degradation and 89.5-98.7% TOC reduction, indicating that the method could be an excellent alternative method to produce truly clean water. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Sunscreens degradation; Photoelectrocatalytic process; TiO2 nanotubular arrays; 4-Methylbenzylidene camphor; 3-Benzophenone; 3,4-Aminobenzoic acid